Movimento estudantil na UFPB: das perseguições à anistia - Costa, Fernando Luiz Araújo da (2022)
This article aims to analyze and comprehend the process of persecution in Federal University of Paraíba (UFPB) students and their access to repair, in the context of transitional justice, from the enactment of the Amnesty Law (act Nº 6683 of August 28, 1979). During the process of “slow, gradual and safe” political opening, the distention began to unravel the military regime instal led in April 1st 1964, which lead to the rise of many women and men fighting for forgiveness and the return of the brazilian men and women who were in exh i le. This research takes place in the new political history, from the view of René Rémond (2003), and seeks to create a dialogue between political history and cultural history by means of the concept of Political History from Serge Bernstein (1998) and Motta (2009). We will introduce the concept of Transitional Justice, as stated by Félix Reátegui (2011) and Tosi and Silva (2014), in order to build theoretical foundation and understanding the concept of this transition in Brazil along with its historical context. We will, then, utilize the sources, the processes of amnesty requests from the Paraiban Association of the Amnestied and the National Commitee of Amnesty, as well as documents from the SNI and the Recife Agency, granted to the Commitee for the Truth and Memory Preservation of the State of Paraiba, currently available as part of the collection of the Democracy Memorial of Paraiba, located at the José Américo House Foundation. This documentation can be considered, in the words of Icléa Thiesen (2013), “sensitive documents”, placed in the limits between historic an d lived memory, produced by the State, therefore primarily characterized as “oficial”, and because they are memory narratives in which the violations to human rights were perpetrated by agents of the brazilian government and “enable the reconstruction of memories “impaired” by torture, clandestinity and violence” ” (CATELA, 2011, p. 386). By virtue of oral history we were able to collect the testimonies of women and men who operated in the Brazilian Committee for Amnesty, João Pessoa section, were then persecuted by the regime and later submitted their requests for amnesty to the National Comitee of Amnesty. Using oral history we could also obtain information on the “daily li fe and the material culture of some people or a specific group” (PORTELLI, 1997, p. 27). Interviews were conducted with some of the individuals whose names have come up from the analysis of documents that reported the people who currently stand out in political militancy, wheter in political parties or in social movements. This project is linked to the extension of History Concentration an d Historic Culture in the line of History and Regionalities of the Post Graduation in History Program of UFPB.